The challenge of education: social perspectives of the teacher - Pacheco Gualdrón, Jorge Eliécer (Rastros Rostros, 2016)
Purpose:  This  essay  reflects  on  the  purposes  of  education  today,  on  the  role  of  teacher and student, and on the importance of the articulation between pedagogy and society.Themes: concepts of education, society, pedagogy, authority and leadership  that  must  be  present  in  the  educational  act  are  considered. Development:  from  some  passages  of  Miguel  de  Unamuno’s  novel: Amor  y  Pedagogía  (Love  and  Pedagogy)  and  using  the  ideas  of  Vigotski,  Franco  Serrano,  Bazán,  among others, as reference points, some ideas on the challenges of current education are presented.Conclusions: this reflection serves to define the roles assumed by teachers and students as beings immersed in a demanding society that poses new challenges.
Keywords: love; education; leadership; Miguel de Unamuno; society